2021
DOI: 10.3390/agronomy11050941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilisation and Inoculation with Bradyrhizobium japonicum on the Fatty Acid Profile of Soybean (Glycine max (L.) Merrill) Seeds

Abstract: Soybean is a valuable protein and oilseed crop ranked among the most significant of the major crops. Field experiments were carried out in 2016–2019 in South-East Poland. The influence of soybean cultivars (Aldana, Annushka), nitrogen fertilizer (0, 30, 60 kg∙ha−1 N) and inoculation with B. japonicum (control, HiStick® Soy, Nitragina) on the content of fatty acids (FA) in soybean seeds was investigated in a three-factorial experiment. This study confirms the genetic determinants of fatty acid composition in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…The detailed methodology of the field experiment is presented in the work of Szpunar-Krok et al [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed methodology of the field experiment is presented in the work of Szpunar-Krok et al [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative interpretation of the chromatograms was performed by comparing the retention times of fatty acid methyl esters in the test sample with those of Supelco 37 fatty acid methyl ester matrices. The detailed methodology for determining the FA profile and its content in soybean seeds is given in the work by Szpunar-Krok et al [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pentadecanoid acid was present in the soybean of the imported soybean variety G196, but absent in the soybean of variety G197 grown in Burkina Faso. In 2021, Szpunar-Krok and Wondołowska-Grabowska showed that soybean fat quality indices were significantly influenced by cultivar type [ 26 ]. For the evaluation of the effect of cultural practices on the nutritional quality of soybeans, the molecular characterization of pesticides allowed for the detection of the four main families of pesticides: carbamates, orgnanochlorines, organophosphates, pyrethroids, as well as triazines, strobin and benzoylurea derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…For this, investigations on mineral nitrogen in soybean seek to better understand the dynamics between BNF and additional supplementation with nitrogen. Among the various factors investigated, we found studies that associate nitrogen doses with sowing density (FERREIRA et al, 2016;WERNER et al, 2016); supplementary mineral nitrogen with its effects on oil and/or protein contents in grains (HAMAGUCHI et al, 2020;MOREIRA et al, 2017;PRUSIŃSKI, BATURO-CIEŚNIEWSKA, BOROWSKA, 2020;SZPUNAR-KROK et al, 2021); nitrogen supply with seed quality (ZUFFO et al, 2021); as well as those that investigate the dynamics of nitrogen absorption in the initial stages of soybean, in which the BNF is not yet meeting the requirements of the crop (CONCEIÇÃO et al, 2018); in addition to studies on the effects of fixed nitrogen in the subsequent crop (GOSS et al, 2002;ZUFFO et al, 2022); and studies on foliar nitrogen and their effects on carbon and oxidative metabolism (RODRIGUES et al, 2021). Bahry et al (2014) pointed out that, in some edaphoclimatic conditions, nitrogen from BNF is not enough to meet the requirements of the crop and its limitation may compromise the final productivity, evidencing that the application of nitrogen in the reproductive phase of soybean positively influences some yield components.…”
Section: Introductionmentioning
confidence: 99%